Strengthening Professional Collaboration and Expertise: Implementing and Sustaining a Hospital School Community of Practice - Miranda Field; Heather Lewis (Continuity in Education)
This practice-based intervention paper describes the design and implementation of a Community of Practice (CoP) intervention for hospital school professionals across three hospital sites in Saskatchewan, Canada. The intervention consisted of four structured sessions per academic year, two mandatory and two optional, offered during school division professional development days. Each session included facilitated dialogue, guest speakers, collaborative planning, and resource sharing tailored to the realities of hospital-based and inclusive education. Structured using Wenger’s theory of social learning and reported following the GREET (Guideline for Reporting Evidence-based practice educational interventions and Teaching) framework, the CoP was conducted from September 2016 through June 2021. It involved elementary and secondary teachers from hospital schools, complex needs programs, mainstream schools, and student teachers, totaling between 7 and 11 participants annually. The intervention aimed to address the unique professional development needs of hospital teachers, mitigate professional isolation, enhance interdisciplinary collaboration, and support evidence-informed practices tailored to students aged 5–17 with complex medical and mental health needs. Data were collected through attendance records, facilitator notes, participant feedback, and reflective forms. Analysis employed a thematic approach using deductive alignment with predefined learning objectives and inductive methods to identify themes. Results indicated the CoP effectively fostered relational trust, professional renewal, adaptable resource co-creation, and sustained engagement despite systemic and bureaucratic constraints. Knowledge translation efforts included podcast interviews, conference presentations, and field trips to showcase and disseminate the CoP model. Recommendations include integrating robust evaluation frameworks at the intervention outset. This intervention provides valuable insights for replicating CoP models, the intervention, within similar interdisciplinary education-healthcare contexts.